1981
DOI: 10.1007/bf01255801
|View full text |Cite
|
Sign up to set email alerts
|

Do husbands and wives agree? Fertility attitudes and later behavior

Abstract: Analysis of the extent to which husbands and wives agree in their attitudes toward a number of key issues that may affect fertility behavior shows that although aggregate views of men and women are remarkably similar, marital couples are frequently in disagreement, particularly if measures discounting for chance agreement of responses are employed. In other words, we cannot accept either the husband or the wife as a surrogate respondent. These conclusions are based on data from cross-sectional surveys in a dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 14 publications
(15 reference statements)
0
23
0
1
Order By: Relevance
“…Men and women have equal influence over the subsequent childbearing outcome and neither the male or the female intention predominates (Miller and Pasta 1995), irrespective of whether the relationship is based on traditional or more equal gender roles (Thomson 1997;Thomson and Hoem 1998). However, in very traditional contexts in which women are still the main and perhaps the sole responsible of childrearing one might expect that men have less influence than women in the implementation of their fertility intentions especially if they live in a traditional union where the female partner does not work (Fried and Udry 1979;Coombs and Chang 1981). More generally, in contexts characterised by low gender equality men who equally share with their partner their household and family tasks may have a stronger fertility decisionmaking power than men who live in more traditional couples.…”
Section: What Criteria Underlie the Resolution Of Partners' Disagreemmentioning
confidence: 99%
“…Men and women have equal influence over the subsequent childbearing outcome and neither the male or the female intention predominates (Miller and Pasta 1995), irrespective of whether the relationship is based on traditional or more equal gender roles (Thomson 1997;Thomson and Hoem 1998). However, in very traditional contexts in which women are still the main and perhaps the sole responsible of childrearing one might expect that men have less influence than women in the implementation of their fertility intentions especially if they live in a traditional union where the female partner does not work (Fried and Udry 1979;Coombs and Chang 1981). More generally, in contexts characterised by low gender equality men who equally share with their partner their household and family tasks may have a stronger fertility decisionmaking power than men who live in more traditional couples.…”
Section: What Criteria Underlie the Resolution Of Partners' Disagreemmentioning
confidence: 99%
“…While this may seem obvious, many studies on the interrelationship between paid work, education, and childbearing focus on women only. Previous research has confirmed that both partners in a couple influence decisions about having children (Beckman 1984;Coombs and Chang 1981;Corijn, Liefbroer, and de Jong Gierveld 1996;Jalovaara and Miettinen 2013;Jansen and Liefbroer 2006;Thomson 1997;Vignoli, Drefahl, and De Santis 2012), but the lack of suitable couple data often causes fertility researchers to focus only on women. This can be problematic because the exclusion of partner information has been shown to lead to an overestimation of the negative effects of women's employment on fertility (Matysiak and Vignoli 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested the closer a man and woman are in their levels of education, and more education they have, more likely are they to discuss and use family planning [24], [25]. A study on women in Togo, Africa showed that if a woman has some control over money then she is more likely to discuss family planning with her husband.…”
Section: Rationalementioning
confidence: 99%